How do we treat wheezing infants? Evidence or anecdote. Issue 6 (1st December 2002) - Chavasse, R J; Bastian-Lee, Y; Seddon, P
Abstract : Consultant paediatricians were questioned about their management of wheezing disorders in infants. Salbutamol was the preferred bronchodilator for recurrent wheeze, whereas ipratropium was preferred in viral bronchiolitis. Doses of both medications varied widely. Both inhaled and oral corticosteroids were considered by most respondents. Practice does not clearly follow guidelines or evidence and presumably continues to be based on anecdote.